KEBIJAKAN PEMERINTAHAN PRESIDEN LUIZ INÁCIO LULA DA SILVA DALAM MENGATASI MASALAH HUTANG LUAR NEGERI BRASIL TAHUN 2003-2010 - Elvi Khairani Putri; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research discusses about the policy taken by the Brazilian President Lula Da Silva through its programs in addressing the foreign debt during his leadership. Past the Brazilian economy which is heavily dependent on foreign debt to international financial institutions. Brazilian foreign debt continues to rise each year. Wrong economic policies undertaken by the early leaders make Brazil stuck in ever-increasing debt. During the Brazilian government controlled by the military regime, the Brazilian economy is getting worse. Foreign debts Brazil is increasing. The number of poor people in the country is increasing. The subsequent years the Brazilian economy and the condition is getting worse due to the pilling up foreign debt following considerable interest.The author analyzes the case using qualitative methods to find data and facts through some literature. The literature was collected from books, journals, mass media and websites. Structuralism is rooted in the thought of Karl Marx or Neo-Classical end that many organizations under the shelter at the New Left movement (the New Left). Lula’s leftist leader focused on socialist policies that concentrate on people’s welfare and poverty alleviation by way of paying off all foreign debt of Brazil.Lula Da Silva of Brazil during her leadership very significant progress with its policies towards the pro underclass One of them is the “Fome Zero” (no hunger) to reduce poverty population. This program, among others, such as the creation of reservoirs in arid regions in Brazil. One of the major programs of the fome Zero policy called “Bolsa Familia”, namely the provision of financial assistance for low income families are poor Economic programs to reduce poverty was considered successful by some circles. However, the most important is Lula Da Silva is considered successful in stabilizing the Brazilian economy.Keywords: Policy, Economic Crisis, Economic Program, Foreign Debt